The Monomeric GTPase Rab35 Regulates Phagocytic Cup Formation and Phagosomal Maturation in Entamoeba histolytica - Verma, Kuldeep (J Biol Chem, 2017)
One of the hallmarks of amoebic colitis is the detection of Entamoeba histolytica (Eh) trophozoites with ingested erythrocytes. Therefore, erythrophagocytosis is traditionally considered as one of the most important criteria to identify the pathogenic behavior of the amoebic trophozoites. Phagocytosis is an essential process for the proliferation and virulence of this parasite. Phagocytic cargo, upon internalization, follows a defined trafficking route to amoebic lysosomal degradation machinery. Here, we demonstrated the role of EhRab35 in the early and late phases of erythrophagocytosis by the amoeba. EhRab35 showed large vacuolar as well as punctate vesicular localization. The spatiotemporal dynamics of vacuolar EhRab35 and its exchange with soluble cytosolic pool were monitored by fluorescence recovery after photobleaching experiments. Using extensive microscopy and biochemical methods, we demonstrated that upon incubation with RBCs EhRab35 is recruited to the site of phagocytic cups as well as to the nascent phagosomes that harbor Gal/GalNAc lectin and actin. Overexpression of a dominant negative mutant of EhRab35 reduced phagocytic cup formation and thereby reduced RBC internalization, suggesting a potential role of the Rab GTPase in the cup formation. Furthermore, we also performed a phagosomal maturation assay and observed that the activated form of EhRab35 significantly increased the rate of RBC degradation. Interestingly, this mutant also significantly enhanced the number of acidic compartments in the trophozoites. Taken together, our results suggest that EhRab35 is involved in the initial stage of phagocytosis as well as in the phagolysosomal biogenesis in E. histolytica and thus contributes to the pathogenicity of the parasite.